2015
DOI: 10.1016/j.ijnurstu.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Positive benefits of caring on nurses’ motivation and well-being: A diary study about the role of emotional regulation abilities at work

Abstract: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription AbstractBackground: Recent research reveals that not all job demands have negative effects on workers' well-being and suggests that the negative or positive effects of specific job demands depend on the occupational sector. Specifically, emotional job demands form the heart of the work for nurses and for this reason they can be interpreted by nurses as a challenge that promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
72
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 49 publications
3
72
0
9
Order By: Relevance
“…Although this is a worthwhile aim, it is crucial for policy makers to consider the risks faced by staff in delivering high quality compassionate care. In accordance with the findings of previous research [25,32], this study has highlighted a strong link between the emotional demands of the caring role and feelings of emotional depletion. Emotional exhaustion will not only affect the wellbeing of healthcare staff, but more indirectly influence the quality of patient care via outcomes such as compassion fatigue [11].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although this is a worthwhile aim, it is crucial for policy makers to consider the risks faced by staff in delivering high quality compassionate care. In accordance with the findings of previous research [25,32], this study has highlighted a strong link between the emotional demands of the caring role and feelings of emotional depletion. Emotional exhaustion will not only affect the wellbeing of healthcare staff, but more indirectly influence the quality of patient care via outcomes such as compassion fatigue [11].…”
Section: Discussionsupporting
confidence: 92%
“…Insight is also needed into how nurses make empathic connections and construct emotional boundaries when interacting with patients and their families and the implications for their wellbeing over time. A diary study conducted by Donoso and colleagues [32] found that the emotional regulation strategies utilised by nurses underpin their reactions to the emotional demands of practice. In order to develop interventions to help nurses manage emotional interactions more effectively and avoid burnout, insight is needed into the type of emotion regulation strategies that can protect or threaten wellbeing and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proporcionan mayor tolerancia al estrés y, por tanto, mayor compromiso o emocionalidad positiva en el trabajo (Blanco-Donoso et al, 2015). En contraste, aquellos profesionales con menores habilidades emocionales se caracterizan por realizar una interpretación más negativa de las demandas del entorno, de su propia -645 -http://dx.doi.org/10.14204/ejrep.43.17068 actividad y de su percepción de auto-eficacia, por lo que ponen en marcha estilos de afrontamiento más desadaptativos (Johnston, Hansen, Birney y Stough, 2010).…”
Section: Introductionunclassified
“…(Corbin, 2008), perhaps justifying some of the disquiet about the limited number of publications in current health care literature dealing with caring or healing. However, both subjects still have a high profile in the nursing literature, including within this journal, which, for example, recently published findings of a study to promote compassionate relationship-centred care for older people, their relatives and staff (Dewar and Nolan, 2013), a study of the positive benefits of caring on nurses' motivation and wellbeing (Donoso et al, 2015) and an elegant qualitative study on the caring culture amongst nurses (Rytterstrom et al, 2009). Jean Watson has written extensively on caring within the nursing profession, and related this to the development of healing relationships (Watson, 1997(Watson, , 2012.…”
mentioning
confidence: 99%